2008
DOI: 10.3989/mc.2008.v58.i291.105
|View full text |Cite
|
Sign up to set email alerts
|

Geopolímeros basados en residuos de la producción de áridos ligeros

Abstract: La geopolimerización es una manera viable para procesar y agregar valor a los residuos industriales de alumino-silicato dando lugar a materiales con elevadas resistencias mecánmicas, alta inercia química y que permiten encapsular otros residuos, incluso peligrosos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
1
0
1
Order By: Relevance
“…It was further confirmed that the choice of the alkaline activator had a significant effect. This agreed with the results reported in a previous study [39], where clay powder burned at temperatures below 950 • C and combined with caustic soda NaOH or slaked lime Ca(OH) 2 was shown to have binding properties. The introduction of alkaline activators, such as sodium hydroxide in these residues, improves the mechanical stabilization of the soil by raising the pH.…”
Section: Discussionsupporting
confidence: 93%
“…It was further confirmed that the choice of the alkaline activator had a significant effect. This agreed with the results reported in a previous study [39], where clay powder burned at temperatures below 950 • C and combined with caustic soda NaOH or slaked lime Ca(OH) 2 was shown to have binding properties. The introduction of alkaline activators, such as sodium hydroxide in these residues, improves the mechanical stabilization of the soil by raising the pH.…”
Section: Discussionsupporting
confidence: 93%
“…These binders result from the chemical interaction between strongly alkaline solutions and a material with high content of amorphous aluminosilicates (fly ash, blast furnace slag, sugarcane bagasse ash, copper slag, construction and demolition waste, among others) [ 7 ]. These new materials, in addition to having excellent mechanical performance, even at short ages, present reduced permeability, chemical and thermal stability, thus constituting high performance materials [ 13 ]. According to McLellan et al [ 14 ] and Yang et al [ 15 ], alkaline-activated or geopolymer cements can have similar environmental problems during their life cycle to those of Portland cement in terms of CO 2 emissions and energy requirements; however, according to Tempest et al [ 16 ] most of the emissions from alkaline activation systems can be attributed to the activator solutions due to the energy consumption associated with their production [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…se ha demostrado, que un material con esas características es posible conseguirlo, aplicando caolín ya que este presenta una relación siO2/al2O3 de 1.2 aplicada por varios autores, definiendo con esto a la geopolimerización como cadenas de aluminio-silicato en las cuales el número de moléculas de silicato pueden variar siendo estas: 1 molécula de silicio polisialato, 2 moléculas de silicio polisialato siloxo, 3 moléculas de silicio polisialato disiloxo todas estas con relación a una molécula de aluminio estabilizadas por unión de un metal alcalino (Davidovits, 1994). estas cadenas se forman por co-polimerización del aluminio y especies de silicato que proceden de la disolución de la alúmina y silicio presente en la constitución química de los materiales en un medio alcalino (P. Soares, 2007) Considerando que el ecuador es rico en arcillas, la primera parte del estudio consistiría en encontrar la química del activador aplicando matrices experimentales tipo 2 k y mediante análisis mineralógicos buscar una relación siO2/al2O3 de alguna arcilla cerámica similar o superior al caolín para llevar a cabo la polimerización.…”
Section: Introductionunclassified